2022
DOI: 10.1186/s12889-022-14027-6
|View full text |Cite
|
Sign up to set email alerts
|

Variation of parental feeding practices during the COVID-2019 pandemic: a systematic review

Abstract: Coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which is highly contagious and has resulted in a protracted pandemic. Infections caused by new coronavirus strains, primarily Delta and Omicron and currently highly prevalent globally. In response to the epidemic, countries, and cities implemented isolation and quarantine guidance, such as limiting social contact, which have affected the lifestyles and quality of life of the popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…An early study among Polish secondary school students during the pandemic reported the increased value of weight control and health determinants, and the decreased value of sensory appeal and mood, with the rest of the determinants equally important compared with the pre-COVID period [9]. Luo et al reviewed reports regarding available changes in parental feeding practices because of the pandemic [10]. He found that parents used various practices of feeding, such as high levels of coercive control and reductions in rules and limits, changes which are expected to affect the food choices of the youngsters when they later become college students.…”
Section: Introductionmentioning
confidence: 99%
“…An early study among Polish secondary school students during the pandemic reported the increased value of weight control and health determinants, and the decreased value of sensory appeal and mood, with the rest of the determinants equally important compared with the pre-COVID period [9]. Luo et al reviewed reports regarding available changes in parental feeding practices because of the pandemic [10]. He found that parents used various practices of feeding, such as high levels of coercive control and reductions in rules and limits, changes which are expected to affect the food choices of the youngsters when they later become college students.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review assessed eating behavior during COVID-19 and indicated changes in food consumption, characterized by an increased frequency of snacking and a preference for sweets and ultra-processed foods over fruits, vegetables, and fresh foods [24]. Among the reasons that could lead to this modification of eating habits during the pandemic are increased food insecurity [10] and the confinement itself, which modified parental eating practices [25] by decreasing people's ability to acquire fresh food, increased consumption of takeout, and a preference for long shelf-life foods to minimize going out to buy groceries [26].…”
Section: Discussionmentioning
confidence: 99%
“…A recent qualitative study that focused on parental strategies for improving children's (ages 9-14) PA during the pandemic found that parents were concerned about low activity levels of their children and made modifications to their lives to support and encourage their children to be active, including taking them to places to be active and seeking activity opportunities (Ostermeier et al, 2022). Generally, elevated child-parent interactions regarding dietary intake and PA have been observed during the COVID-19 pandemic (Eyler et al, 2021;Luo et al, 2022;Szpunar et al, 2022), with some engagement positive (i.e. : making changes to encourage activity) and some negative (i.e.…”
Section: Discussionmentioning
confidence: 99%